Is the Child Perceptions Questionnaire for 11–14 year olds sensitive to clinical and self-perceived variations in orthodontic status? - Locker D, Jokovic A, Tompson B, Prakash P. (Blackwell Synergy, 2007)
To assess the association between scores on the Child Perceptions Questionnaire for 11–14 year olds (CPQ11–14) and clinical and selfperceived measures of malocclusion.